New observational method for prediction of one-dimensional consolidation settlement - Guo, Wei (2017)
The Chapman–Richards model is adopted in this paper to best fit the Terzaghi's one-dimensional consolidation curve. The obtained formula fits the theoretical solution well, with a regression coefficient R2 of 0·9995 and an error of less than 2%. By adopting this model, a new method to predict the ultimate settlement and the coefficient of consolidation using monitoring settlement data is proposed. The accuracy of the proposed method is verified against oedometer test and field monitoring data. For the cases verified, the ultimate settlement predictions from the proposed method are more reliable than those from the Asaoka's method for the different range of settlement data.